Perfil e avaliação dos participantes de um curso de formação continuada em práticas educacionais inclusivas na modalidade a distância - Capellini, Vera Lúcia Messias Fialho [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Valle, Tania Gracy do [UNESP]; Melchiori, Lígia Ebner [UNESP]; Zanata, Eliana Marques [UNESP]; Leite, Lucia Pereira [UNESP]; Lepre, Rita Melissa [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2011)
This article analyses aspects related to a continuing education course about Inclusive and Special Education in the area of Mental Disabilities offered to 20 (twenty) groups of teachers by the Ministry of Education. The Distance Course was offered in different regions of Brazil with a 180 (a hundred and eighty) hours workload. The research included the profi le of the participants, an evaluation of the course by the participants and the analysis of the dropout causes. The aspects of the course under evaluation received a positive evaluation by most of the participants. The most frequent reason for the dropout rates include participants’ limitations in terms of meeting deadlines, personal reasons and diffi culties in using computers. It was concluded that Distance Education seems to be a relevant tool for the acquisition of knowledge about inclusive practice.

Este artigo analisa aspectos relacionados a um curso de formação continuada sobre práticas em Educação Especial e Inclusiva na área de Defi ciência Mental, oferecido a professores de 20 (vinte) turmas inscritas pelo Ministério da Educação, de diferentes regiões do Brasil, com 180 (cento e oitenta) horas de duração, por meio de EaD. A pesquisa envolveu a descrição do perfi l dos cursistas, uma análise da avaliação do curso realizada pelos cursistas e a das causas da evasão ocorrida no curso. Os resultados indicaram que os participantes, na sua maioria, avaliaram o curso positivamente em todos os aspectos solicitados. Os motivos mais frequentes para a evasão referiram-se às limitações dos cursistas, como a difi culdade em cumprir os prazos, motivos pessoais e inabilidade em usar computador. Concluiu-se que a Educação a Distância mostra-se como ferramenta relevante para aquisição de conhecimentos sobre a prática pedagógica inclusiva.
Profile and evaluation of participants in distance learning continuing education courses about inclusive practices in education
Keywords: Distance Learning; Inclusive Education; Continuing Education; Ensino a Distância; Educação Inclusiva; Formação continuada